2020
DOI: 10.3390/su12197995
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis as a Tool in Environmental Policy for Sustainability: The Case of Waste Recycling Projects in the Republic of Serbia

Abstract: Modern consumer society uses an increasing number of products to meet its needs, which become waste after use, thus posing a serious problem that threatens sustainable development. Investment in waste recycling, due to a high level of non-financial benefits, is considered sustainable, especially in the End-of-life Vehicles (ELV) and Waste Electrical and Electronic Equipment (WEEE) recycling areas. The research objective of this paper is to test the sensitivity of the model for sustainable management of recycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Circular Economy (Bakker et al, 2014;Iraldo, Facheris and Nucci, 2017;Zhang et al, 2019;Arcos et al, 2020;Denčić-Mihajlov, Krstić and Spasić, 2020;Hischier and Böni, 2021;Mishra, Verma and Tiwari, 2021) The Circular Economy aims to contribute to the closing of the life cycle of products, aiming for greater durability, resource savings, and waste minimization (Iraldo, Facheris and Nucci, 2017). Its initiatives are receiving public attention in order to pressure global business authorities to meet Circular Economy principles (Hischier and Böni, 2021).…”
Section: Content Analysismentioning
confidence: 99%
“…Circular Economy (Bakker et al, 2014;Iraldo, Facheris and Nucci, 2017;Zhang et al, 2019;Arcos et al, 2020;Denčić-Mihajlov, Krstić and Spasić, 2020;Hischier and Böni, 2021;Mishra, Verma and Tiwari, 2021) The Circular Economy aims to contribute to the closing of the life cycle of products, aiming for greater durability, resource savings, and waste minimization (Iraldo, Facheris and Nucci, 2017). Its initiatives are receiving public attention in order to pressure global business authorities to meet Circular Economy principles (Hischier and Böni, 2021).…”
Section: Content Analysismentioning
confidence: 99%
“…Low availability of waste treatment facilities on regional and national levels, for management of end-of-life motor vehicles (Stojanovic [24]; Hogg [25]; Von Schoenberg [26] Low level of investments for infrastructure development necessary for motor vehicle dismantling (Dencic Mihajlov [27]; Marstijepovic [28])…”
Section: Economic and Market Trends Environment Issuesmentioning
confidence: 99%
“…It is necessary to create conditions for the treatment of hazardous waste, to preserve the environment and human health, and consequently provide the conditions for circular economy implementation (Stevanovic-Carapina et al 2016). Denčić-Mihajlov et al (2020) conclude that state subsidies have an imminent impact on the recycling of cars and refrigerators in the Republic of Serbia, especially in electronic waste recycling. Management of different types of waste in Serbia was investigated in the context of the circular economy.…”
Section: Waste Managementmentioning
confidence: 99%
“…They concluded that the state of the circular economy in Serbia is in an unenviable position. The circular economy in Serbia has not been implemented in practice yet, but experts from several fields are dealing with this topic (Ilić &Nikolić, 2016;Stevanovic-Crapina et al 2016;Milanović et al 2020;Denčić-Mihajlov et al 2020;Demirović Bajrami et al 2020;Schmit et al 2020;Dudjak et al 2021;Rakascan et al 2021;Kosanović et al 2021;Bucea-Manea-Țoniş et al 2021).…”
Section: The State Of Circular Economy In Serbiamentioning
confidence: 99%